2005
DOI: 10.1039/b419143a
|View full text |Cite
|
Sign up to set email alerts
|

Alkyne metathesis

Abstract: This review discusses the emergence of alkyne metathesis as a valuable synthetic tool applicable in the synthesis of complex molecules and polymer science.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
204
0
9

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 386 publications
(213 citation statements)
references
References 121 publications
0
204
0
9
Order By: Relevance
“…Our previous investigations have shown that ring-closing alkyne metathesis (31)(32)(33)(34) combined with Lindlar hydrogenation is a highly adequate tool for the stereospecific formation of the macrocyclic rings in the parent compounds 1 and 2 (27,28). This strategy, which is exemplarily outlined for 2 in Scheme 2, therefore constitutes a conserved design element en route to all analogues prepared herein.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous investigations have shown that ring-closing alkyne metathesis (31)(32)(33)(34) combined with Lindlar hydrogenation is a highly adequate tool for the stereospecific formation of the macrocyclic rings in the parent compounds 1 and 2 (27,28). This strategy, which is exemplarily outlined for 2 in Scheme 2, therefore constitutes a conserved design element en route to all analogues prepared herein.…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27] In contrast to the more widely practiced ring-closing alkene metathesis (RCM) reaction, [28] RCAM ensures a stereoselective entry into macrocyclic (Z)-alkenes when combined with a Lindlar semireduction of the cycloalkynes primarily formed. The projected RCAM cases B!A and D!C, however, are highly demanding since the catalyst must rigorously distinguish between the triple-and the double bonds of the substrates; whereas the former must be activated, the latter must remain untouched.…”
Section: Resultsmentioning
confidence: 99%
“…As outlined in the Results and Discussion section (Scheme 1), this target constitutes a particularly stringent test for ring-closing alkyne metathesis (RCAM). [25] Not only must the chosen catalyst be able to rigorously distinguish between the p-system of the alkynes on the one hand and the olefins on the other hand, even though the latter are conjugated and hence electronically coupled, but the metathesis event also has to build up considerable strain: note that the resulting product embodies an (E)-configured olefin in addition to the a priori linear acetylene moiety in its bicyclic meta-bridged edifice that incorporates a 16-membered ring. Although model studies on alkyne-selective enyne-yne metathesis reactions provided encouraging preA C H T U N G T R E N N U N G cedence with regard to the chemoselectivity issue, the smallest cycle so far to be successfully forged by this transformation was an 18-membered ring.…”
Section: -Epi-latrunculin Bmentioning
confidence: 99%
“…Such a reaction allows obtaining at will the Z or E stereochemistry of the double bond by further control of the hydrogenation of the triple bond. In that context, Fürstner has applied his trisamidomolybdenum complex as a catalyst precursor for the synthesis of several natural products and the reader will find most of his results in a recent review [40].…”
Section: Applicationsmentioning
confidence: 99%